Purification of Glucomannan of Porang (Amorphophallus oncophyllus) Flour using Combination of Isopropyl Alcohol and Ultrasound-Assisted Extraction - Dyah Hesti Wardhani; Lucia H Rahayu; Heri Cahyono; Hana L Ulya (Dept. of Chemical Engineering, Diponegoro University, 2020)
Porang tuber is rich of glucomannan content but contained irritable compounds to be consumed. Ultrasound-assisted extraction (UAE) using isoprophyl alcohol (IPA) was developed as a purification method for glucomannan. This study aimed to determine the effects of UAE conditions (IPA concentrations, ratios of solvent-solid, and number of extraction stages) on the characteristics of purified glucomannan (PG) from porang flour (PF). Single-stage UAE using 80% IPA concentration and ratio of solvent-solid of 8:1 (ml/g) for 10 min gave the highest glucomannan content (76.10%). At this condition, the PG viscosity and yield were 12,800 cP and 96.10%, respectively. Furthermore, the three-stage UAE using 80% IPA concentration in each stage improved the glucomannan content to 83.26% with 15,960 cP and 90.02% of yield. The morphology showed that the purified glucomannan powders had smoother surface and less crump after the purification. Both carbonyl and acetyl groups were observed on PF and PG in different intensities. Keywords: glucomannan, isopropanol, Amorphophallus oncophyllus, ultrasound-assisted extraction